(untitled) (Hong Kong Journal of Ophthalmology, 2007)
Aim: To compare the visual outcomes of photodynamic therapy with verteporfin and transpupillary thermo- therapy for subfoveal occult choroidal neovascularization secondary to age-related macular degeneration. Patients and methods: Patients with subfoveal occult choroidal neovascularization caused by age-related macu- lar degeneration were included in this non-randomized open-label prospective comparative clinical trial. Stand- ardized refraction, visual acuity testing, serial color photo- graphy, and fundus fluorescein angiography were performed to evaluate the effects of treatment in 16 eyes of 15 patients who underwent photodynamic therapy and 15 eyes of 13 patients who underwent trans- pupillary thermotherapy using standardized treatment protocols. Follow-up was carried out at 1, 3, and 6Â months. Retreatment was carried out after 3 months, if indicated. Results: There was no significant difference in visual acuity pre- and post-treatment for patients undergoing photodynamic therapy and transpupillary thermotherapy at 1, 3, and 6 months. In patients with visual acuity >=6/12 and lesions >4 disc area, there was a significant risk of severe visual loss with photodynamic therapy (p = 0.0005). Conclusion: For patients with subfoveal occult choroi- dal neovascularization with visual acuity Â³6/12 and lesions >4 disc area, there is a significant risk of severe visual loss with photodynamic therapy. However, if the visual acuity is <6/12, both photodynamic therapy and transpupillary thermotherapy are effective for short-term preservation of visual acuity.